Similarities and Differences Between Staphylococcal and Streptococcal Toxic Shock Syndromes in Children: Results From a 30-Case Cohort - Javouhey, Etienne; Bolze, Pierre-Adrien; Jamen, Claire; Lina, Gerard; Badiou, Cédric; Poyart, Claire; Portefaix, Aurelie; Tristan, Anne; Laurent, Frédéric; Bes, Michèle; Vandenesch, François; Gilletand, Yves; et al. (Frontiers in Pediatrics, 2018)
Toxic shock syndromes (TSS) are severe shocks due to staphylococcal or streptococcal infection that require specific treatments. The early recognition of these shocks is crucial to improve their outcomes. Objectives The primary objective of this study was to compare characteristics and outcomes of TSS in children, in order to identify putative early clinical diagnostic criteria. Secondary objectives were to determine the toxin gene profiles of associated isolated strains and the relevance of measuring Vβ T-cell signatures to confirm diagnosis. Study design We performed a multicenter retrospective evaluation of clinical data, biological results, and treatment outcomes of children with a confirmed or probable case of staphylococcal or streptococcal TSS. Children were consecutively included if they were admitted to the pediatric intensive care units of Lyon (France), between January 2005 and July 2011. Results Among the 30 analyzed children, 15 presented staphylococcal TSS and 15 streptococcal TSS. The most frequent origin of staphylococcal and streptococcal TSS was the lower respiratory tract (53%) and the genital tract (47%) respectively. Non-menstrual cases presented more frequently with neurological alterations, and digestive signs were predominant in menstrual forms. Compared to Staphylococcal TSS, Streptococcal TSS presented with higher organ dysfunction scores (median Pediatric Index of Mortality 2 score 20.9 (4.1-100) vs 1.7 (1.3-2.3), p=0.001), required respiratory support more frequently (80% vs 33%, p=0.02) , were intubated for a longer time (3 days (0.75-5) vs 1 day (0-1.5), p=0.006) and had a non-significant trend of higher case-fatality rate (20% vs 7%, p=0.60). The lack of antitoxin therapy was associated with higher case-fatality rate (50% vs 4%, p=0.04). The Vβ repertoire measurements exhibited toxin dependent-alterations in accordance with the toxin gene profiles of isolated strains in both types of TSS. Regarding toxin gene profiles, 10/15 Staphylococcus aureus belonged to clonal complex (CC) 30 and 6/12 Streptococcus pyogenes were emm1 type suggesting clonal etiologies for both TSS. Conclusion Despite the involvement of functionally similar toxins, staphylococcal and streptococcal TSS differed by their clinical signs, origin of infection and prognosis. The detection of Vβ profiles was useful to confirm the diagnosis and for the identification of involved toxins.